Peranan Teori Belajar Humanistik untuk Meningkatkan Efektifitas Pembelajaran - Habsy, Bakhrudin Al; Afkar, Dzakiyul; Nejwa, Nawaf Nur; Nurkumalasari, Parisca (Lembaga Yasin AlSys, 2024)
In this research, researchers want to examine how to understand humanistic learning theory to increase learning effectiveness. Humanistic education aims to make humans whole so that individuals can understand changes in the environment and themselves by paying attention to human values. In this case, the education model places much hope on the pragmatic value of science and technology, and cannot kill interests and humanity. Therefore, humanities education can help students develop in a better direction and improve their abilities to face life's challenges in the future. In today's digital era, a humanistic approach to education remains relevant and important to implement. In his research, the research method used by the researcher was a quantitative method through library research. The research object of this research is to study humanistic learning theory to increase learning effectiveness. The benefit of this research is to change an individual's attitude or behavior, from what was initially bad because they didn't know it to good. Getting individuals used to acting democratically, participatively, and humanely. The results of this research can be said that by understanding students' learning styles and types of intelligence, teachers can use learning methods, strategies, and models that suit students' learning styles and types of intelligence. Thus, the existence of humanistic learning theory will make learning that takes place in the school environment more interesting and meaningful for students, because students learn using learning styles and intelligence.